The interpretation of dispositivity as a basis for the realization of contract freedom - Kozikava, Iryna (Journal of the Belarusian State University. Law, 2019)
In article the author brings up a question of limits of freedom of the contract in the context of interpretation of norms of civil law as dispositive or imperative. On the basis of the analysis of doctrinal sources and law enforcement, positions of researchers concerning freedom of the contract and model of imperativeness of legal instructions are systematized. Legal and social -economic prerequisites for introduction of a basic presumption of a dispositivity as the principle of civil law are revealed, specific proposals on improvement of the current legislation of Republic of Belarus, regarding modification of Art. 2 of Civil Code for the purpose of legalization of a dispositivity as the principle of civil law are made and proved. In development of this proposal the mechanism of realization of the principle of a dispositivity which is recommended for fixing at the level of the resolution of the Plenum of the Supreme Economic Court of Republic of Belarus «About using of the provisions of the Civil code of the Republic of Belarus regulating the conclusion, change and cancellation of contracts» is developed.
Keywords: civil contract; freedom of the contract; dispozitivity; method; principle of civil law